Heat Management Strategy for All‐Inorganic, Full‐Spectral Concentrator CsPbBr3/Bi2Te3‐Integrated Solar Cells. Issue 10 (2nd August 2022) - Guo, Qiyao; Zhao, Yuanyuan; Tang, Qunwei; Duan, Jialong
Abstract : A solution to breaking through the Shockley–Queisser efficiency limit of solar cells is to increase the irradiation intensity beyond one standard sun by means of fabricating concentrator photovoltaics (CPVs). Herein, it is demonstrated that the power conversion efficiency (PCE) of carbon‐electrode, all‐inorganic CsPbBr3 perovskite solar cell (PSC) can be enhanced to 10.08% under 5 suns from 8.94% under one sun. The efficiency improvement mainly contributes to the especially boosted open‐circuit voltage ( V oc ) up to 1.643 V, which is delivered by the high‐irradiation enlarged quasi‐Fermi‐level splitting in CsPbBr3 perovskite film. The substantially detrimental heat induced by carbon electrode owing to its full‐spectral absorbance to light is further used by integrating a Bi2 Te3 thermoelectric generator (TEG) into this all‐inorganic CsPbBr3 PSC to play the role of refrigerant under concentrated light condition. The CsPbBr3 /Bi2 Te3 ‐integrated device achieves a PCE of 12.46% with an ultrahigh V oc of 2.114 V by the photovoltaic–thermoelectric principle. More importantly, the integrated solar cell maintains over 90% of the initial efficiency after 150 h irradiation under 5 suns, suggesting a great potential to enhance efficiency by fabricating integrated perovskite/thermoelectric devices. Abstract : By integrating Bi2 Te3 ‐based thermoelectric generator with all‐inorganic CsPbBr3 perovskite solar cell to form concentrator CsPbBr3 /Bi2 Te3 ‐integrated solar cell, a champion efficiency up to 12.46% with an ultrahigh open‐circuit voltage of 2.114 V has been achieved by photovoltaic–thermoelectric principle under 5 suns irradiation owing to the full‐spectra absorbance.